Rehabilitation of visual disorders after brain injury - Zihl, Josef (Neuropsychological rehabilitation., 2010)
This thoroughly updated and extended edition covers the various cerebral visual disorders acquired after brain injury, as well as the rehabilitation techniques used to treat them. These are described within a brain plasticity framework, using data from single and group case studies along with follow up observation data. This original, tailor-made approach also includes the recording of eye movements for assessing scanning performance in scene perception and reading. The book gives a brief synopsis of the historical background on the subject, alongside an outline of intervention designs and meth.